The impact of intelligent systems on the compensation policies of companies of the future - Lopes da Costa, R.; Filipa, T.; Martinho, F.; Gonçalves, R.; Dias, Á.; Pereira, L. (International Journal of Intelligent Enterprise, 2023)
Even though intelligent systems bring numerous benefits to organisations, the challenges that may occur in their functionality are still of concern, as revealed in the literature. The implementation of technologies has been growing, leading organisations to become advantageous and competitive, increasing productivity as well as reducing the functions performed by humans. Managers cannot devalue their employees, because they have the help of machines and initially feel difficulties in their adaptation. To understand the connection between the subjects of intelligent systems and compensation policies, the research questions will address the impact of intelligent systems on the compensation policies of the companies of the future and the impact that these technologies will have on rewards and employee appreciation. To answer these questions, a questionnaire was launched, and the results are analysed using a quantitative model, which showed that operation and non-operation benefits of using intelligent systems will positively affect compensation policies and that risks of its implementation are not a main concern.